E-Commerce Coins in Shopee: The Perspective of Madzahibul Arba’ah on Halalness and Digital Economic Practices - Unzilah Khomairoh (Al-Fiqh: Journal of Contemporary Islamic Law, 2025)
This study examines the permissibility of using Shopee coins in the Shopee application from the perspective of the four major Islamic schools of thought (Madhahibul Arba'ah) and its implications for digital economic practices. Shopee coins are a non-cash incentive that can be used to receive discounts on future transactions. The research employs a qualitative-descriptive approach, utilising literature studies and comparative fiqh analysis from the Hanafi, Maliki, Syafi’i, and Hanbali schools. The study finds that, in general, the use of Shopee coins does not violate the basic principles of muamalah, provided it does not involve usury (riba), uncertainty (gharar), or gambling (maisir). Since the coins function solely as discounts and cannot be converted into cash, they are classified as grants or sharia bonuses. All four schools of thought agree that bonuses for buying and selling are permitted, provided there is no fraud or ambiguity in the contract. This research underscores the need to adapt fiqh law to modern digital innovations and highlights the importance of digital economic fiqh education. By understanding the legal status of digital incentives like Shopee coins, the public can better navigate online transactions and avoid misunderstandings regarding new economic systems.